2019
DOI: 10.1080/25783858.2019.1589988
|View full text |Cite
|
Sign up to set email alerts
|

Guardians of research: negotiating the strata of gatekeepers in research with vulnerable participants

Abstract: Gatekeepers are an integral part of an ethical process of seeking authorisation for research. The number of gatekeepers, and the negotiations between researchers and gatekeepers, become more complex for research which includes children and young people (CYP) and other vulnerable groups. Ethical researchers and gatekeepers share a desire to protect CYP from harm. This paper examines the multifaceted nature of gatekeepers and the positive and negative influences upon their decision-making. The traditional view o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…These questions support the researcher to consider who they wish to involve in the research and the rationale for their involvement. The researcher is also encouraged to consider who will need to be asked for informed consent; for example, which strata of gatekeepers will need to be consulted for their permission (Kay 2019). The consultation with gatekeepers will be examined more deeply later in this paper.…”
Section: Participant Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…These questions support the researcher to consider who they wish to involve in the research and the rationale for their involvement. The researcher is also encouraged to consider who will need to be asked for informed consent; for example, which strata of gatekeepers will need to be consulted for their permission (Kay 2019). The consultation with gatekeepers will be examined more deeply later in this paper.…”
Section: Participant Factorsmentioning
confidence: 99%
“…Thus, the strata of gatekeepers comprise adults who are both external to, and internal within, the research context (Bryman 2016). These strata are identified within the participant factors boxes of the proposed framework and will include University Ethics Committees, Headteachers, Parents and CYP (as 'auto gatekeepers' [Kay 2019]). Gatekeepers hold a mutual responsibility for safeguarding CYP within the other functions they fulfil.…”
Section: The Intersections Between Consent Assent and Issues Related To Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Those who grant permission are called gatekeepers, especially in studies involving children and young people (Webster, Lewis and Brown, 2014;Walford, 2001). Kay (2019) proposed a strata of gatekeepers involved throughout the research process, starting with the University ethics committee, as described above. Next, Kay (2019, p.43) suggested that the most appropriate person to seek permission from is the 'organisational gatekeeper'.…”
Section: Gate Keepingmentioning
confidence: 99%